PHYSICAL EDUCATION AS A PRACTICE OF FREEDOM (Fiep Bulletin - online, 2013)
The Physical Education has a wide variety of expressive elements of body culture as games and games thus make available to create new ways to generate significant improvement, facilitating the teaching-learning process. Thus, teaching and learning reflect a conditional that is not being prevented from expressing himself, or that effectively expresses itself, is the objective of the present work. The survey was then classified as exploratory literature sources such as Paulo Freire and Kunz, plus other interesting the way, was chosen the dialectical method, which allows the observation of the production of works that serve as justification for the search. Thus, it is expected to aspire to the challenge of freeing people, students living surface that anything can respect and even without awareness of faith in myself and in others and in connection depressive invirtuosa to act in education, especially in Physical Education. Anyway, our intention is to try to show through research PE lessons in humility, hope and love, combined with education on learning mediated dialogue.
Keywords: physical education; liberation; dialogue